(untitled) - Crystal, Billy (Los Angeles, CA, 2011)
Sex always gets in the way of friendships between men and women. At least, that's what Harry Burns believes. So when Harry meets Sally Albright and a deep friendship blossoms between them, Harry's determined not to let his attraction to Sally destroy it. But when a night of weakness ends in a morning of panic, can the pair avoid succumbing to Harry's fears by remaining friends and admitting they just might be the perfect match for each other?
Keywords: Phim, rạp chiếu phim,Films, cinema